Analisis Kesalahan Fonologi Dalam Keterampilan Membaca Teks Bahasa Arab Siswa Kelas V MI Baiquniyyah - Desi Rahmania Zulfa (Mahira: Journal of Arabic Studies & Teaching, 2023)
The process of Arabic learning often encounters various kinds of problems during the learning process. This is indeed something that is common because Arabic itself is not the mother tongue or the first language for the learners who learn it, because they are basically non-indigenous people. One of the problems in the process of learning Arabic is errors in terms of phonology in arabic, these errors include vocal errors, consonant errors, diphthong errors, multiple consonant errors, and clothing errors. Some of these mistakes are serious problems that exist in learning Arabic, because from these mistakes will give birth to various other errors including in the meaning of Arabic sentences that do not match the intended essential meaning. Therefore, with this research, it is hoped that it can help teachers and students in learning Arabic by studying these various kinds of errors so that they can be corrected and can achieve the objectives of learning Arabic well.